Religion, terrorism and public goods testing the club model - Berman, Eli 1960-; Laitin, David D. 1945- (Working paper series / National Bureau of Economic Research, 2008)
Can rational choice modeling explain why Hamas, Taliban, Hezbollah and other radical religious rebels are so lethal? The literature rejects theological explanations. We propose a club framework, which emphasizes the function of voluntary religious organizations as efficient providers of local public goods in the absence of government provision. The sacrifices religious clubs require are economically efficient (Iannaccone (1992)), making them well suited for solving the extreme principal-agent problems faced by terrorist and insurgent organizations. Thus religious clubs can be potent terrorists. That explanation is supported by data on terrorist lethality in the Middle East. The same approach explains why religious clubs often choose suicide attacks. Using three data sources spanning a half century, and comparing suicide attackers to civil war insurgents, we show that suicide attacks are chosen when targets are "hard," i.e., difficult to destroy. Data from Israel/Palestine confirm that prediction. To explain why radical religious clubs specialize in suicide attacks we model the choice of tactics by rebels attacking hard targets, considering the human costs and tactical benefits of suicide attacks. We ask what a suicide attacker would have to believe to be rational. We then embed that attacker and other operatives in a club model. The model has testable implications for tactic choice and damage achieved by clubs and other rebels, which are supported by data on terrorist attacks in the Middle East: Radical religious clubs are more lethal and choose suicide terrorism more often, when they provide benign local public goods. Our results suggest benign tactics to counter terrorism by religious radicals.